2021
DOI: 10.1155/2021/5511041
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B2 (CCNB2) Stimulates the Proliferation of Triple-Negative Breast Cancer (TNBC) Cells In Vitro and In Vivo

Abstract: Triple-negative breast cancer (TNBC) is the most aggressive type of breast cancer. Currently, targeting therapy makes great advances for the treatment of TNBC, whereas more effective therapeutic targets are urgently needed. Cyclin B2 (CCNB2), which belongs to B-type cyclins, is known as a cell cycle regulator. CCNB2 is synthesized at G1 phase in cancer cells and downregulated at anaphase. The defects of CCNB2 led to the abnormal cell cycle and tumorigenesis. Though there are wide effects of CCNB2 on multiple t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…CCNB2 also found to promote cell cycle progression resulting in tumorigenesis in case of triple negative breast cancer (Wu et al, 2021). It was also identified in the cell cycle progression leading to poor prognosis of HCC (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…CCNB2 also found to promote cell cycle progression resulting in tumorigenesis in case of triple negative breast cancer (Wu et al, 2021). It was also identified in the cell cycle progression leading to poor prognosis of HCC (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…CCNB2 (cyclin B2) is a member of the B-type cyclins family that can interact with p34cdc2, and is a critical component of the cell cycle regulation [ 48 ]. CCNB2 has been shown to promote the proliferation of triple-negative breast cancer cells in vitro and in vivo [ 49 ]. As validated by a comprehensive bioinformatics study, CCNB2 has been identified as a promising therapeutic target for ovarian cancer [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that the knockdown of circ_ CCNB2 increased the radiosensitivity of PCa through repressing autophagy by the miR-30b-5p/KIF18A axis, but no biological function of CCNB2 in prostate cancer has been found ( Cai F. et al, 2020 ). CCNB2 was highly expressed in human triple-negative breast cancer (TNBC) tissues and correlated with the prognosis and clinical pathological features ( Wu et al, 2021 ). However, the key targets of CCNB2 in TNBC and its biological functions remain to be found.…”
Section: Discussionmentioning
confidence: 99%